Andrew Johnson - Burgan, Michael (Minneapolis, Minn. : Compass Point Books, 2003)
A biography of the seventeenth president of the United States, from his humble beginnings as a tailor in North Carolina through his controversial term as the first post-Civil War president and beyond.
The rise and fall of a common man -- The young tailor -- A rising political star -- Preserving the Union -- Battling Congress -- The former president.
Includes bibliographical references (p. 60-61) and index.
Keywords: Johnson, Andrew, -- Juvenile literature; Johnson, Andrew; Presidents -- Biography -- United States; Presidents